Digital Transformation of Manufacturing Enterprises: An Empirical Study on the Relationships between Digital Transformation, Boundary Spanning, and Sustainable Competitive Advantage - Fang Xue; Xiaokang Zhao; Yunqing Tan (Discrete Dynamics in Nature and Society)
This paper investigates the relationships between digital transformation, boundary spanning, and sustainable competitive advantage of manufacturing enterprises through an analysis of data from 127 manufacturing enterprises. Our main research findings are as follows. First, digital transformation has a positive impact on sustainable competitive advantage of manufacturing enterprises. Compared with the degree of transformation, technology readiness has a stronger influence on sustainable competitive advantage. Second, digital transformation has a positive impact on boundary spanning of manufacturing enterprises. Third, boundary spanning of manufacturing enterprises has a positive impact on their sustainable competitive advantage. Fourth, digital transformation affects the acquisition of sustainable competitive advantages of enterprises through boundary spanning, where the direct role of digital transformation accounts for 75% and the mediation effect of boundary spanning accounts for 25% of the total effect. Fifth, the mediation effect of boundary spanning on the relationship between digital transformation and sustainable competitive advantage is mainly realized through boundary spanning depth, while the mediation effect of boundary spanning breadth on the relationship between digital transformation and sustainable competitive advantage is insignificant. Our findings can help realize the digital transformation of manufacturing enterprises and achieve their sustainable competitive advantage.